Engineering miniature CRISPR-Cas Un1Cas12f1 for efficient base editing - Yueer Hu; Linxiao Han; Qiqin Mo; Zengming Du; Wei Jiang; Xia Wu; Jing Zheng; Xiao Xiao; Yadong Sun; Hanhui Ma (Elsevier, 2024)
Adeno-associated virus (AAV) is a relatively safe and efficient vector for gene therapy. However, due to its 4.7-kb limit of cargo, SpCas9-mediated base editors cannot be packaged into a single AAV vector, which hinders their clinical application. The development of efficient miniature base editors becomes an urgent need. Un1Cas12f1 is a class II V-F-type CRISPR-Cas protein with only 529 amino acids. Although Un1Cas12f1 has been engineered to be a base editor in mammalian cells, the base-editing efficiency is less than 10%, which limits its therapeutic applications. Here, we developed hypercompact and high-efficiency base editors by engineering Un1Cas12f1, fusing non-specific DNA binding protein Sso7d, and truncating single guide RNA (sgRNA), termed STUminiBEs. We demonstrated robust A-to-G conversion (54% on average) by STUminiABEs or C-to-T conversion (45% on average) by STUminiCBEs. We packaged STUminiCBEs into AAVs and successfully introduced a premature stop codon on the PCSK9 gene in mammalian cells. In sum, STUminiBEs are efficient miniature base editors and could readily be packaged into AAVs for biological research or biomedical applications.